新加坡书城的文化记忆 ：论百胜楼的困境与转型 = Cultural memory of Singapore’s City of Books : a study of Bras Basah Complex’s predicament and transformation - 林芷瑜 Lim, Zhi Yu (Nanyang Technological University, 2020)
新加坡的华文书店在20世纪60年代与70年代时期，分布在中央商业区萊佛士坊及罗敏申路、乌节路、大坡、小坡这几个地区。当时，逛书店占据了人们生活中的一大部分，为人们提供乐趣与精神粮食。随着国家的发展，70年代城市重建展开后，新加坡建屋发展局于1980年建立百胜楼。当时，百胜楼以“书城”为名号，成为了当时的热门景点。然而，如今的百胜楼却面临着书店倒闭，热潮退却的问题。本论文以文化记忆理论为基础，以社会层面为中心，将“店家”和“市民”锁定为研究的主要对象。通过采访百胜楼的店家以及对市民的问卷调查，了解到消费者习惯与喜好的改变是导致百胜楼客源不足的主要原因。此外，电商的出现也对百胜楼的实体店造成了强烈的冲击。为了能应对这一系列的危机，百胜楼选择了转型，将百胜楼打造成“文化旅游区”，不断的举办各种文艺活动。然而，百胜楼还是未能满足现代消费者的需求。百胜楼只有跟随社会的步伐，找出自己的定位以及加强宣传，方能保存文化记忆和保护其延续性。 In the 1960s and 1970s, Singapore's Chinese bookstores were distributed in Raffles Place, Robinson Road, Orchard Road, South Bridge Road and North Bridge Road area. In those times, visiting bookstores occupied a large part of people's lives, bringing joy, satisfaction, and inspiration to ones’ mind. With the country’s development, the urban redevelopment began in the 1970s, and Singapore Housing and Development Board established the Bras Basah Complex in 1980. At that time, Bras Basah Complex was known as "City of Books" and soon became popular. However, today's Bras Basah Complex is facing the problem of persistently low footfall, with bookstores struggling to stay afloat. This thesis is based on the theory of cultural memory, centered on the social level, and focuses on the stores and citizens as the main objects of research. Through conducting interviews with shop owners and assistants of Bras Basah Complex and questionnaire surveys by citizens, it is understood that changes in the consumer behaviour is the main reason for the drop in sales in Bras Basah Complex. In addition, the emergence of e-commerce has also a strong impact on the businesses of the physical stores. To cope with this series of crises, Bras Basah Complex chose to transform into a "Cultural Tourism Area" , which continuously hosts various cultural and artistic activities. However, Bras Basah Complex still failed to meet the needs of modern consumers. For Bras Basah Complex to preserve its cultural memory, it must discover its position in today’s society and strengthen its publicity.